The Production of Ecological Expert Knowledge on the Wetlands of the Parana Delta: The Place of the Local People? - Dayan, Laura-Azul (2025)
Introduction: The Paraná Delta is considered a macrosystem of wetlands in a good state of conservation that is being affected by anthropic activities. Today, a plurality of actors coexist who conceive and inhabit this territory in different ways. Objective: This paper analyzes the place that experts in ecology give to the people of the Paraná Delta and their knowledge in the production of scientific scholarship about these wetlands. Methodology: Ecological experts were interviewed as part of a research with an ethnographic approach. A corpus of ecological papers collecting studies carried out in the area between the 1980s and 2023 was built and subjected to a qualitative documentary analysis. Conclusions: The first years’ documents were the foundations of ecological knowledge of these wetlands, with a conception of nature as excluding man. As the years passed, the documents increasingly described the ecosystem and focused on the causes of its degradation, diagnosing anthropogenic damage, and proposing strategies to reverse it. The use of the category “local inhabitants and producers” is scarce at the beginning and abundant in the framework of ecosystem services, however it is homogenizing. Based on the interviews, divergent views were found between what some experts think about the territory and its people and what they express in their written productions.